Architectural design contest with social participation as a part of building culture in Europe - Kowalczyk, Maciej Wojciech (Journal of Education Culture and Society, 2018)
Thesis. The culture of organising architectural competitions has a long tradition in Europe. The architectural desgin contest is used as a democratic tool for selecting the best design solution. In today’s European building culture there is a constantly growing need for the social input into the  design process. In effect, architectural competitions are facing changes. On the one hand, an architectural design contest needs to fulfill the EU’s legal frames. On the other hand, the traditional forms of competions are questioned by society, that is searching for a more transprent selection process.Methods. The study shows the concept of the building culture (Baukultur) as an ideological background of all the building activity in Europe. It describes the role of an architectural competition as an instrument for the high quality development. The author shows current legal frameworks for the design contests included in the EU directives and presents different competition practices in Europe with a focus on Poland.Results. There are not many examples of architectural competitions that anticipate the social input. It is an effect of not adjusted procurement law. Nevertheless, some exceptions have already been made.Conclusions. The main difficulty in architectural design contest with social participation is the need of maintaining the legal framework  based on the anonymity of the participant. The social input in the case hampers the preservation of this condition, hence various attempts to modify the existing, traditional formulas.